A robot-aided visuomotor wrist training induces motor and proprioceptive learning that transfers to the untrained ipsilateral elbow - Zhu, Huiying; Wang, Yizhao; Elangovan, Naveen; Cappello, Leonardo; Sandini, Giulio; Masia, Lorenzo; Konczak, Jürgen (Journal of neuroEngineering and rehabilitation, 2023)
Learning of a visuomotor task not only leads to changes in motor performance but also improves proprioceptive function of the trained joint/limb system. Such sensorimotor learning may show intra-joint transfer that is observable at a previously untrained degrees of freedom of the trained joint.